2007
DOI: 10.1517/14740338.6.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric side effects of efavirenz therapy

Abstract: The non-nucleoside analogue inhibitor of the reverse transcriptase, efavirenz (EFV), has become commonly used in highly active antiretroviral combination therapy in the treatment of HIV infection. Although being effective in suppressing plasma viral load, neuropsychiatric side effects have been reported in individuals treated with EFV. There are early complications, such as acute psychosis resembling reactions to LSD intake, as well as nightmares occurring for several days up to 4 weeks after the start of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 44 publications
0
50
0
3
Order By: Relevance
“…This finding is consistent with other studies where the most severe toxicity effects of EFV treatment have been consistently reported within the first 2-4 weeks after treatment initiation and symptoms generally cease after 6-8 weeks. 17,18 There are also reports suggesting that as many as half of patients may develop delayed neuropsychiatric disorders with EFV. 19,20 Although the incidence of EFV-associated ADRs was low in this study, they were severe enough to result in the substitution of EFV in almost half of the patients with reported ADR.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other studies where the most severe toxicity effects of EFV treatment have been consistently reported within the first 2-4 weeks after treatment initiation and symptoms generally cease after 6-8 weeks. 17,18 There are also reports suggesting that as many as half of patients may develop delayed neuropsychiatric disorders with EFV. 19,20 Although the incidence of EFV-associated ADRs was low in this study, they were severe enough to result in the substitution of EFV in almost half of the patients with reported ADR.…”
Section: Discussionmentioning
confidence: 99%
“…More severe cases, consisting of depression, delusions, suicidal ideation and paranoid reactions, have been reported in 0.4 -1.6% of EFV-treated patients (Staszewski, 1999;Hawkins, 2005;. These side effects usually appear within the first few days of treatment and are resolved after 2-4 weeks, although there are cases in which they continue to manifest themselves for several months or even longer periods (Muñoz-Moreno, 2009;Arendt, 2007). The clinical evidence available, though extensive, is insufficient to clarify the mechanisms underlying EFV-induced CNS alterations, but recent data implicate neurotoxic events induced by HIV itself and cytokine production by EFV.…”
Section: Cns Toxicitymentioning
confidence: 99%
“…One major presentation of nNRTI related toxicity is neuropsychiatric disturbances. While NVP-induced CNS side effects, including impaired consciousness and psychotic episodes, have been rare, 40-70% patients on an EFV-containing cART regimen present with a range of CNS-related symptoms, such as insomnia, mood changes, and impaired attention span and concentration (Arendt, de Nocker et al 2007). …”
Section: Side Effectsmentioning
confidence: 99%